Repigmentation of vitiligo‐associated leukotrichia after autologous, non‐cultured melanocyte‐keratinocyte transplantation. (8th July 2013) - Al Jasser, Mohammed I.; Ghwish, Bassel; Al Issa, Ahmed; Mulekar, Sanjeev V.
Abstract: Background: Many cases of leukotrichia are associated with vitiligo. Hair follicles are believed to be the source of melanocytes for skin repigmentation using standard medical therapy for vitiligo. Vitiliginous areas with overlying leukotrichia usually fail to achieve repigmentation by conventional medical treatments as a result of a deficient melanocyte reservoir. Even after the successful repigmentation of vitiliginous skin by medical therapies, leukotrichia hairs may remain depigmented, causing a major psychological impact to the patient. In such cases, surgical treatments may help to achieve the repigmentation of leukotrichia hairs. Reports of successful repigmentation in leukotrichia using different surgical treatments for vitiligo are few. Objective: This study reports the benefit of autologous non‐cultured melanocyte‐keratinocyte transplantation (MKT) in patients with vitiligo‐associated leukotrichia. Methods: We report four cases of vitiligo‐associated leukotrichia treated with MKT. Results: All four patients showed significant repigmentation in vitiligo‐associated leukotrichia after MKT. Conclusions: Melanocyte‐keratinocyte transplantation may represent a good therapeutic option for the repigmentation of vitiligo‐associated leukotrichia. This series includes only four responsive cases. Larger prospective studies are needed to determine the true response rate and mechanism of repigmentation.